Wpływ zmian w marketingu na obszary badań marketingowych - Garbarski, Lechosław (Influence of Changes in Marketing on the Areas of Marketing Research, 2006)
New important changes in market conditions could be observed recently. They caused changes in marketing concepts as direct consequences. As the result of these changes, measurement of ne phenomena, not intensively explored by marketing research before, is necessary. Increasing role of marketing metrics could be perceived as an important challenge for marketing research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 343-350